LEGAL RHETORIC AND PERSUASION IN PLEADINGS: A COMPARATIVE STUDY BETWEEN THE CONTINENTAL AND COMMON LAW SYSTEMS - Жоровля, Эльвира; Tudor, Pașcaneanu (SWorldJournal, 2026)
European legal rhetoric has deep roots in the Roman tradition and classical revival, fundamentally influencing how legal professionals communicate and persuade within modern judicial systems. The article explores the evolution of legal pleadings across tw